Influencia del crecimiento económico en la reducción de la pobreza para la costa peruana: análisis de pool de datos 2007-2017 - Sunción Albán, Katherine (2024)
The objective of the research is to determine how much economic growth influences the reduction of poverty, through the historical analysis of the statistical series of GDP and poverty of the departments of the Peruvian coast 2007-2017. For which the basic type research was carried out with a correlational level, using the data pool methodology, with a database of 110 observations having poverty as endogenous variable and economic growth valued as Domestic Product as exogenous variables. Gross per capita (hereinafter GDPpr), employment, public investment and illiteracy; in which the data was processed through the Ordinary Least Squares method. In this way, the results showed that the GDP per capita contributes 1.07% to the reduction of poverty, while public investment influences 1.85% and employment 0.18%, likewise, a positive link was discovered between the levels of illiteracy and poverty of 0.21%; being able to determine the influence of the variables analyzed in the reduction of poverty.